2005
DOI: 10.1097/01.bsd.0000129586.68729.bb
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preload Magnitudes and Orientation Angles on the Cervical Biomechanics

Abstract: The findings of the current study were important for the further understanding of the cervical biomechanics during in vitro testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…В последнее десятилетие большое внимание уделяется сравнению биомеханических характеристик передних стабилизирующих конструкций (пластин, стержней, кейджей), применяемых при операциях в разных, чаще всего в мобильных шейном и поясничном, отделах позвоночника [50,55,59,65,78,91,96,107,118,124].…”
Section: рисunclassified
“…В последнее десятилетие большое внимание уделяется сравнению биомеханических характеристик передних стабилизирующих конструкций (пластин, стержней, кейджей), применяемых при операциях в разных, чаще всего в мобильных шейном и поясничном, отделах позвоночника [50,55,59,65,78,91,96,107,118,124].…”
Section: рисunclassified
“…However, previous research has been reported that the cervical spine cadaver specimens collapsed under a very low levels of load, much lower than the physiological compressive load in vivo [2]. Therefore, it appears that the traditional in vitro experimental methods rarely include the compressive loads similar to those experienced in vivo, especially in the studies of multi-level cervical spine [3].…”
Section: Introductionmentioning
confidence: 99%
“…Follower load has been used to simulate the physiological compressive load of the human spine and most previous research has reported that its value in the cervical spine was usually beyond 100 N [4][5][6][7]. To quantify biomechanical behavior of the human spine under the follower load, researchers have performed various in vitro experiments and finite element (FE) studies by applying compressive loads [3,6,[8][9][10][11][12][13][14][15]. However, most experimental studies to date have focused on the lumbar spine [8][9][10][11], with only a few experimental studies evaluating the effect of the compressive load on the cervical spine [3,6,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to the CT technique, direct digitization of dried or embalmed cadaveric bones may provide excellent geometric fidelity at the expense of an extensive period of time (15,26,27,28,40,41,50). Another major concern in FE modeling of the spine involves the material properties of the spinal components, which vary broadly, even within a specific structure.…”
Section: Fe Model Of the Cervical Spinementioning
confidence: 99%